THE INFLUENCE OF TECHNOLOGICAL PARAMETERS OF DRYING ON THE CONTENT OF INULIN IN CHICORY AND JERUSALEM ARTICHOKE POWDER - D. O. Eryomenko; Y. V. Osmanova (Современная наука и инновации)
Optimal drying modes of chicory root and Jerusalem artichoke tubers have been experimentally determined in order to preserve the inulin polysaccharide, which has a prebiotic effect, to obtain a powdered semi-finished product of a functional orientation.